Accuracy of MRI-Compatible Contrast Media Injectors - Saake, M.; Wuest, W.; Becker, S.; Uder, M.; Janka, R. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To analyze the exactness of MRI-compatible contrast media (CM) injectors in an experimental setup and clinical use.Materials and Methods: Ejected fluid volumes and amounts of CM were quantified for single and double piston injections. The focus was on small volumes, as used in pediatric examination and test-bolus measurements. Samples were collected before and after clinical MRI scans and amounts of CM were measured.Results: For single piston injections the volume differences were minimal (mean difference 0.01 ml). For double piston injections the volume of the first injection was decreased (mean 20.74 ml, target 21.00 ml, p < 0.01). After a position change of the Y-piece of the injection system, the amount of CM differed significantly from the target value (mean 1.23 mmol and 0.83 mmol at 1 ml/s flow rate, target 1.00 mmol, p < 0.01), independently of the wait time. The clinical samples confirmed these findings.Conclusion: The pistons of modern CM injectors work exactly. However, for small CM volumes the injected amount of CM can differ significantly from the target value in both directions. Influence factors are an incomplete elimination of air and exchange processes between the CM and saline chaser in the injection system.Key Points:• In MRI examinations of children and test-bolus measurements, small amounts of CM are used.• The accuracy of single piston injections is high.• In double piston injections the injected amount of CM can differ significantly from the target value.Citation Format:• Saake M, Wuest W, Becker S et al. Genauigkeit von MRT-kompatiblen Kontrastmittelinjektoren. Fortschr Röntgenstr 2014; 186: 253 – 259
Keywords: MR imaging; contrast agents; gadolinium